Cost of logging accidents : preliminary results of some case studies - Manikam, Doraisingam (1985)
Very little is known about the cost of logging accidents except compensation and medical expenses. This paper attempts to illustrate the nature of accident costs in general, and in logging, in particular. Logging accidents involve both direct and indirect costs. Two cases on fatal accidents indicate that the indirect cost is at least four times the direct cost. The total cost of a major or fatal accident can be very high. Non-injury accidents involving heavy machinery involve high costs particularly in hill operations. An accidents-prevention program is an effective means of reducing accident costs. Logging companies should seriously consider the incorporation of safety programs into their logging operations.